Effects of Interactions Between Individuals and Spatial Dynamics on The Spread of Infectious Diseases using Voronoi Tessellation and The Ising Model - Hızal, Şeyma Firdevs; Bulut, Hasan (My University, 2025)
This study investigates the spatial distribution of individuals within a randomly distributed sample population and their interactions with an infectious disease. For this purpose, an Ising model enhanced with Voronoi tessellation is used to create a more realistic framework for modeling disease spread. The model simulates the process of spreading infectious disease by considering the interactions between individuals and their movement dynamics. The sample population in this study was created for simulation purposes only and is not based on actual demographic of epidemiological data. To assess the infectiousness in the model, the parameter J, defined as the transmission coefficient, is analyzed.
Keywords: Voronoi Tessellation; Ising Model; Monte Carlo Simulations; Metropolis Algorithm; Disease Spread; Epidemiological Modeling